Work Environment and Compensation's Effect on Employee Performance: Mediating Role of Job Satisfaction - Agustina Agustina; Tinik Sugiarti (Universitas KH. Abdul Chalim Mojokerto, 2025)
This thesis aims to examine the influence of the work environment and compensation on employee performance with job satisfaction as an intervening variable. This study employs a quantitative research approach using a survey method, with data collection carried out through questionnaires. The sampling technique used is purposive sampling. Data was collected by distributing questionnaires to 120 employees of PDAM Kota Tarakan. The analysis method applied is Partial Least Squares (PLS). The results of this study indicate that the work environment positively affects employee performance, the work environment positively affects job satisfaction, compensation positively affects employee performance, compensation positively affects job satisfaction, job satisfaction positively affects employee performance, the work environment positively influences employee performance through job satisfaction as an intervening variable, and compensation positively influences employee performance through job satisfaction as an intervening variable.